St. Vincent and the Grenadines : Staff Report for the 1999 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This 1999 Article IV Consultation highlights that during 1990-98, St. Vincent and the Grenadines' real annual GDP growth and inflation averaged 4 percent and 3 percent, respectively. Tourism's importance to the economy grew, and agriculture's fell, with other sectors' contributions remaining relatively stable. In 1999, real GDP growth and inflation are expected to slow to about 4 percent and 2 percent, respectively. The overall public sector surplus is expected to increase slightly about 1 percent of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet